Flood Risk and River Conservation: Mapping Citizen Perception to Support Sustainable River Management - Scaini, Anna; Stritih, Ana; Brouillet, Constance; Scaini, Chiara (Frontiers in Earth Science, 2021)
Involving citizens in river and flood risk management is critical for risk reduction and sustainable development within river basins, but local community input is often limited. This is partly due to the difficulty of quantifying the perceived values and risks related to the rivers, because these are based on personal knowledge and opinions. There is a need for more data on locals’ opinions and how they are spatially distributed across the river basin. Studies analyzing how perceived risks match evidence-based data can be a first step to including local knowledge in the decision-making process and pose the basis to enhance preparedness. Here, we present a blueprint questionnaire to characterize the perception of flood risk and its spatial distribution across the river basin. Respondents are asked their perception of the role of the river in terms of flood risk and management, as well as to pinpoint on a map the areas they identify as the most dangerous during floods. The approach is tested on the Tagliamento River in the Italian Alps, characterized by debates regarding flood protection, flood management and ecological conservation. The flood risk perception map shows good agreement between perceived risk and existing flood risk assessment maps in the lower basin, where major floods happened in recent memory (1966). In the upper basin, despite having suffered frequent floods, participants are more uncertain about the risks. There is interest in being involved in the risk management debate, and most respondents believe that risk reduction and river conservation are compatible. Land use planning is identified as a factor that can increase flood risk. The results point to the necessity to tackle together conservation, risk management and land use planning in order to develop risk-oriented river management strategies. Our study demonstrates how online participatory mapping can be used to improve the understanding of citizens’ perceptions and expectations with regards to their river, and support participation in sustainable river management.